Analisis Kinerja Bagian Tata Pemerintahan Dan Kerjasama Daerah Kabupaten Seram Bagian Barat - Liline, Koce; Nataniel, Elake; Rolobessy, Mike J (Patria Artha University, 2025)
This study analyzes the performance of the Governance and Regional Cooperation Section of West Seram Regency. The analysis focuses on the effectiveness and efficiency of the section's implementation of its duties and functions in supporting the achievement of regional government goals. This study uses a quantitative, qualitative, or mixed approach, collecting data through interviews, document studies, observations, and questionnaires. The study is expected to provide a comprehensive overview of the section's performance and provide recommendations for future performance improvement. The results of this study indicate that the performance of the Governance and Regional Cooperation Section of the West Seram Regency Regional Secretariat is not optimal due to the lack of implementation of several programs.